Militarization and War - Schofield, J. author. aut Link
X, 236 p.
Keywords: This book looks at the influence of military regimes in seven cases: Pakistan in 1965, India in 1971, Israel in 1956 and 1967, Egypt in 1973, Iran in 1969 and Iraq in 1980. The author contends that countries with military governments are warlike not because they glorify war, but rather because they are poorly equipped to manage diplomacy.